Phthalic Acid and Its Role in Roots of Melon Plants (Cucumis melo) - Sixto A. Marquez; Kevin M. Crosby; Bhimanagouda S. Patil; Amir M. H. Ibrahim; Carlos A. Avila; Herika P. Pessoa; Jashbir Singh (PhytoFrontiers, 2024)
Melon is an important crop worldwide. However, this crop has many problems, such as high production costs, pests, diseases, and sensitivity to abiotic stresses. Among the diseases that negatively impact its production, vine decline disease (VDD), caused by the fungus Monosporascus cannonballus, is very dangerous because it affects the plant when the fruit is almost ready to be harvested, which causes huge losses to growers. In addition, this disease is widely spread in areas where melons are grown all over the world, and its control through soil fumigation is costly and polluting. Thus, cheap and sustainable ways to combat it must be found. Therefore, this study was conducted with the objectives of identifying and quantifying phenolic compounds produced during the interaction of melon plants with the fungus M. cannonballus, which can be useful in controlling VDD, ameliorating cultural practices of this crop, and consequently reducing production costs. Two varieties were grown and inoculated with the fungus M. cannonballus: TAM-Uvalde (susceptible) and USDA PI 124104 (resistant). Their roots were sampled before inoculating with the fungus (0 h) and 24, 48, and 72 h after inoculation. The root chemicals were then analyzed using high-performance liquid chromatography. Our results indicate that phthalic acid was induced in the roots after inoculation in both varieties, which suggests that it is produced by the plant as a defensive compound. Also, the production of phthalic acid varied over time according to the variety used, which suggests its allelopathic function. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.